ETIKA KOMUNIKASI DALAM PENDIDIKAN ISLAM: UPAYA MENGURANGI BULLYING MELALUI MEDIA INFOGRAFIS INTERAKTIF DI SEKOLAH DASAR ISLAM AL AZHAR 13 RAWAMANGUN - Sulistia Salsabiilaa; Raihanna Zahwa; Taftazani Ulya Fauzan; Faqih Fathul Ihsan (CV. ADIBA AISHA AMIRA, 2025)
Bullying is a problem that is widespread in the surrounding environment, both in schools and in the community. In the educational context, communication ethics has an important role in preventing bullying. Communication ethics can help and regulate how to communicate between individuals. Bullying is something we are no stranger to hearing because we often encounter it either in person or on social media. This is done for personal satisfaction and lack of sympathy for others. In this research, the aim was to reduce the occurrence of bullying in the school environment which was carried out in elementary schools, with the research subjects being grade 5 students at Al-Azhar 13 Rawamangun Islamic Elementary School. This research uses interactive infographic learning media which shows that the use of interactive infographics based on Islamic communication ethics can reduce bullying and increase students' understanding of good communication ethics. It is hoped that this research can provide awareness and prevent bullying.